Archivist competency development in higher education: Do training and certification truly make a difference? - Istiyani Nuryati; Sulustiyati Aeni Amroatun; Adhitya Eka Putri; Fajria Renietaningtyas Masyrurroh; Fajar Sri Purwanti; Rosidatul Jalilah Hernawati Fathurrahman (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The competency of archivists plays a critical role in ensuring effective records management and institutional accountability in higher education, particularly amid rapid digital transformation. This study is motivated by the limited competency of archivists at Universitas Negeri Yogyakarta, especially in technical archival skills and adaptation to digital systems. The research aims to examine the effectiveness of training and certification programs in enhancing archivists’ competencies, identify supporting and inhibiting factors, and explore their implications for career development. A qualitative descriptive approach was employed, with data collected through in-depth interviews, direct observation, and document analysis. Data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing, supported by source triangulation to ensure validity. The findings reveal that training programs significantly improve archivists’ technical skills and professional confidence, while certification provides formal recognition and strengthens professional legitimacy. When implemented synergistically, training and certification contribute to higher levels of professionalism, adaptability, and career advancement among archivists. This study concludes that well-structured training and certification programs are effective mechanisms for enhancing archivist competency and credibility in higher education institutions, offering practical insights for human resource development and archival management policies.